The Impact of a Quality Management System on the Efficiency of Operations in a Company - Julian Jakubowski; Katarzyna Łasińska; Roman Stryjski (Communications of International Proceedings, 2020)
The primary focus of quality management is to meet customer requirements and to strive to exceed customer expectations. Every aspect of customer interaction provides an opportunity to create more value for the customer. Understanding current and future needs of customers and other interested parties contributes to sustained success of the organization. The work provides an assessment of the use and effectiveness of the quality management methods used by the selected company. Methods, tools and principles for supporting and building quality were analyzed not only during production. Areas that are constantly in need of improvement and objectives that can be achieved in accordance with the principle of continuous improvement are distinguished, affecting the degree of implementation of the customer's requirements. The results of the improvements carried out are described, according to the individual tools.
Keywords: Quality Management; Overall Equipment Effectiveness